EVALUASI STRUKTUR ATAS PADA GEDUNG RUMAH SAKIT GRAND MITRA MEDIKA MEDAN – SUMATERA UTARA - Robinson Sidjabat; Rahelina Ginting; Ricky Yohanes Marbun (Prodi Teknik Sipil Fakultas Teknik Universitas Darma Agung, 2020)
Grand Mitra Medika Hospital is an important part of the health system; therefore in the construction of this hospital, a strong and safe building structure is required. Evaluation and analysis of building structures is done by looking for general data, project technical data and information that supports the planning of structures such as structural drawings, loading to be used and their criteria. The calculation of the structure of this building is reviewed against dead load, living load, wind load and earthquake load in accordance with SNI-1727-2013 and SNI-1726-2012 regulations. For structure analysis created 3-dimensional building model with the help of SAP2000 application to get moment style, sliding style, and axial force so that the repetition of the structure can be calculated in accordance with sni-2847-2013 regulations. From the calculation of each element of the structure obtained thick plate reinforcement 15 cm x direction = D10-150 ; direction y = D10-200, bending reinforcement beam 30x70 on the pedestal = 9D19, field = 7D19 and shear reinforcement = D10-100, column bending reinforcement = 28D25 and shear reinforcement = D13-125.